Design and fabrication of printed fuse - John Trublowski; Robert S. Douglass; Nilay Mehta; Rajen Modi (2025)
A power fuse for protecting an electrical load subject to transient load current cycling events in a direct current electrical power system is provided. The power fuse includes at least one fuse element assembly that includes an elongated planar substrate, a plurality of fusible weak spots, and a conductor. The weak spots are formed on the substrate and are longitudinally spaced from one another on the substrate. The conductor is separately provided from the substrate and the weak spots. The conductor includes a solid elongated strip of metal having no stamped weak spot openings therein and therefore avoiding thermal-mechanical fatigue strain in the conductor when subjected to the transient load current cycling events. The solid elongated strip of metal includes coplanar connector sections that are mounted to respective ones of the weak spots and obliquely extending sections bent out of plane of the connector sections to extend above the substrate.